Renal Neuroendocrine Tumor: A Cat in the Box - Rijhsinghani, Archana N (Annals of Pathology and Laboratory Medicine, 2025)
Neuroendocrine tumors of the genitourinary tract are rare tumors. Considering the exhaustive list of the latest classification of renal neoplasms, renal neuroendocrine tumor is the last resort to the unanswered diagnosis in histopathology and always comes as a surprise after extensive work-up.